On the Grounding Status of Appositive Relative Clauses - Koev, Todor (Proceedings of the Amsterdam Colloquium, 2011)
The prevalent assumption in the literature is that appositive relative clauses (ARCs) contribute asserted but backgrounded content (see B¨ oer & Lycan [4], Chierchia & McConnell-Ginet [5], Bach [3], Dever [7], Potts [14], AnderBois et al. [2]). In this paper I demonstrate that ARCs are not inherently backgrounded. Rather, clause-medial ARCs are backgrounded whereas clause-final ARCs behave like regular foreground content. I propose a uniform semantics for ARCs which de rives their grounding status from whether they are processed before or after the content contributed by the main clause is accepted by the addressee. The idea is formally implemented in Dynamic Predicate Logic (Groenendijk & Stokhof [11]) enriched with propositional variables (An derBois et al. [2]).